Seed dormancy status of tropical weedy rice population in Malaysia - Amalia Qistina Zulrushdi,; Nur Ardiyana Rejab,; Muhamad Shakirin Mispan, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Seed dormancy is a trait that promotes the survival of weedy rice (Oryza sativa L.) in the rice seed bank. Weedy rice displays different level of dormancy depending on several factors including genetic control. Determining seed dormancy status of weedy rice is crucial to understand adaptive mechanism of the weed in the rice agroecosystem especially in the tropic regions. To investigate the degree of seed dormancy of weedy rice, 66 weedy rice seed samples were collected from Selangor rice fields. The degree of seed dormancy was determined by standard germination test at 7, 14, 21, 42, 49, 56, 63, and 284 days after imbibition. The dormancy status of weedy rice after >200d in room temperature storage was compared. A total of 92.4% of weedy rice samples displayed a high degree of dormancy upon maturation. The germination rates of sampled weedy rice are divergent, indicating weedy rice in the tropical regions has variation in the degree of seed dormancy. The cumulative germination rate was gradually increased over time and reached total dormancy loss at 284 days after the initial imbibition. The germination rate of weedy rice after >280 days in dry storage displayed a bimodal distribution pattern, with 25.8% and 18.2% of sampled weedy rice showed a strong and weak seed dormancy, respectively. This study showed that weedy rice seeds in Malaysia displayed a high degree of seed dormancy and can retain their viability more than 200d once imbibed. This trait can enhance the survivability of weedy rice in the tropical rice agroecosystems.